A scoping review of nutritional interventions and policy guidelines in the interconception period for prevention of noncommunicable diseases. Issue 1 (5th July 2022) - Watson, Daniella; Jacob, Chandni M.; Giles, Gareth; McAuliffe, Fionnuala M.; Godfrey, Keith; Hanson, Mark
Abstract: Introduction: The interconception period is considered a time when parents are likely to engage with health messages and are in frequent contact with healthcare professionals. Through this scoping review and policy analysis, we synthesized articles and guidelines on interconception care to provide recommendations to improve health outcomes for parents, infants and future generations. Methods: Four databases were searched systematically, using Medical Subject Headings and free‐text terms based on 'interconception' and 'postpartum.' Selected articles included systematic reviews, pilot studies and guidelines on interconception and postpartum interventions published globally and in English by UK public health organizations and government agencies between 1 January 2010 and 12 January 2021. Thirty percent of titles, abstracts and full‐text papers were double‐screened. The description table of identified guidelines was used as a template to qualitatively generate key categories, which later developed into a framework of six domains. Findings are described using a narrative synthesis approach. Results: We found 47 documents with guidelines, 29 systematic reviews and 6 pilot studies on interconception and postpartum care. Six domains were generated as follows: interconception care, nutrition‐specific, nutrition‐sensitive, personal‐centred care, health professional, and multistakeholder approach. Interconception care opportunities include the postpartum period, family planning, routine practice and risk assessments. Health and nonhealthcare professionals with roles to play in the interconception period include general pratitioners, health visitors, dieticians, nutritionists, health psychologists, community groups, local authorities and charities such as Tommy's and First Step Nutrition. Conclusions: The interconception and postpartum periods offer crucial opportunities to intervene, to reduce possible long‐term effects of suboptimal nutrition. Although the policy analysis for this scoping review focused on the United Kingdom, the literature review had a global focus and the recommendations can have wider implications for other countries.